URBAN DEVELOPMENT TOOLKIT FOR CLIMATE CHANGE: CRITICAL REVIEW OF STATE INTERVENTION IN PRAXIS - Mihajlov, Vladimir (Journal of Economic Development, Environment and People, 2012)
This paper aims to review the various forms of state intervention in urban planning, and its purpose is to reconsider guidelines for solving problems in cities, caused by climate change. After World War II, urban planning was guided by centralized state management, in the scope of progress and social justice. State intervention was recognized as an instrument for creating new models of the city spatial organization. However, because of the new market conditions arising, the policies about Urban Development came in the focus again, in order to control global influences, mainly climate change (the costs of construction, environmental pollution and hazards). It is therefore necessary to return again to the public intervention in urban planning. This will not be easy, because it has to be consistent with democratic freedoms; some of them should be strengthened, and some limited to ameliorate the effects of climate change. In conclusion, the set of general guidelines is expected, in order to translate the policy measures for climate change mitigation, into the instruments urban development is controlled by. Therefore, the changes in defining of building codes are expected, as well as the standards for energy conservation and land-use control (zoning, taxes and urban regulations, etc.).